Modus operandi and the socio-spatial milieu in which immigrant niche markets vis-a-vis informal economic activities - Mhandu, John; Ojong, Vivian Besem; Muzvidziwa, Victor N. (School of Social Work, 2021)
This paper is situated within a broader economic, socio-anthropological framework and set against the background of immigrant niche marketing. Drawing on literature on immigrant niche markets (Gemici, 2008:9; Eckstein and Peri, 2018:3) with specific reference to Africa (Ojong, 2005:12; Ojong and Fomunyam, 2011:23), this paper poses that there is invisible literature aimed at assessing the position of niche markets of Zimbabwe migrant women hairdressers in Durban. Against this backdrop, the ongoing paper presents a succinct position of niche marketing research drawing insights on anecdotal evidence of the abovementioned participants. The initial part of this paper provides an understanding of the dynamics of immigrant niche marketing and its operationalization. The second part of this paper provides an analysis on the multiple avenues utilized by the abovementioned participants in order to startup and sustain their businesses in the host country. Key submission made in the section is that social capital, personal savings, and stokvels play a significant role in starting up informal economic activities of the said participants. The penultimate part of this article discourses how Zimbabwe migrant women hairdressers in Durban experience the concept of mixed embeddedness as they participate in informal economic activities. In this paper, we have engaged with fieldwork data, relevant literature, Giddens structuration theory (2003) and Waldinger et al (1990) interactive model of entrepreneurship growth. We conclusively argue that structural synergies of mixed embeddedness as experienced by the said participants are both enabling and constraining and forms that backbone of their enterprise in the host country.